Athletes' career transition out of sport: a systematic review - Park, S.; Lavallee, D.; Tod, D. (International Review of Sport and Exercise Psychology, 2013)
The purpose of this study was to provide a systematic review of studies on athletes' career transition out of sport from 1968 until the end of 2010. A total of 126 studies were evaluated and reported in three sections: sample characteristics, research designs and correlates of athletes' career transition adjustment. Samples ranged from 1 to 1617. Investigators examined a wide range of competitive levels, both genders and various sports. Researchers have used qualitative (44%), quantitative (44%), and mixed-model (12%) designs. Variables correlated to athletes' career transition adjustment were categorized into factors related to career transition (e.g., self-identity) and available resources during the career transition process (e.g., social support). The discussion focuses on the current status of the study area, limitations in its knowledge, suggested practical implications (e.g., providing proactive support) and future research directions (e.g., examining athletes' retirement decision-making process).